Impact of Men with Undescended Testis on Fertility and Hormonal Function Promoting Hypogonadism (Bangladesh Journal of Medical Science, 2023)
Objectives: Undescended testes or cryptorchidism is a disorder in men and is associated with hypogonadism and infertility. UDT is the majority factor in male adults. Studies on the effects of UDT on hormoneassociated hypogonadism are limited.Materials and Methods: This study aimed to assess the effects of UDT on fertility and testicular hormonal function in adult men. Data from medical records were gathered, laboratory tests, and retrospective interviews from 2018 to 2020. The independent variable was men with UDT, while the dependent variable was fertility and reproductive hormones that trigger hypogonadism. Data on infertility, reproductive hormones, semen analysis, and symptoms of hypogonadism from 20 patients with and without UDT. ANOVA, Kruskal-Wallis test, Pearson chi-square test, and Fisher’s exact test helped perform the analysis.Results and Discussion: Undescended testes were associated with infertility so that levels of FSH and LH were considerably greater than men without UDT (p < 0.05). Bilateral UDT men had the highest levels of FSH and LH but not significantly different from unilateral UDT (p > 0.05). Bilateral UDT men had the lowest mean estradiol, testosterone and sperm quality (p < 0.05). All men had prolactin and AMH levels within normal limits (p > 0.05). Men with UDT had more significant hypogonadal symptoms (p < 0.001)Conclusion: Infertility, FSH, and LH levels were highest in men with bilateral UDT, but testosterone and estradiol levels were lowest. It also has the worst sperm quality and the most hypogonadal symptoms. All of the men had normal prolactin and AMH levels.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 859-868